Confined Ru‐catalysts in a Two‐phase Heptane/Ionic Liquid Solution: Modeling Aspects. Issue 2 (25th November 2020) - Kobayashi, Takeshi; Kraus, Hamzeh; Hansen, Niels; Fyta, Maria
Abstract: A modeling approach for atomic‐resolution studies of sup‐ ported ionic liquid phase (SILP) catalytic systems in silica mesoporous confinement with surface hydroxyl and functional groups is proposed. First, a force field for the Ru‐based catalyst is developed. Second, its solvation behavior within a bulk two‐phase system of heptane and an IL is studied. Third, static and dynamic properties of the confined system are investigated. Using classical molecular dynamics simulations, experimentally inaccessible properties can thus be studied that are important for an optimization of a SILP system for performing a ring‐closing metathesis reaction. Abstract : Learning about confinement effects : Atomistic simulations model nanoconfined molecular catalysts in small mesopores within the supported ionic liquid phase (SILP) technology in view of linker‐free immobilization of the catalysts and enhancement of the reaction selectivity. The model provides important insight towards an optimal tuning of the environment for the reaction.